Bifurcation of cycles of parabolic systems with small diffusion - Klevchuk, I.I. (Yuriy Fedkovych Chernivtsi National University, 2015)
We prove the existence of periodic solutions of autonomous parabolic system of differential equations with small diffusion on the circle. We consider the problem of existence and stability of traveling waves in the equation of spin combustion and Hutchinson equation.
Біфуркація циклів параболічних систем із малою дифузією
Клевчук, І. (1). Біфуркація циклів параболічних систем із малою дифузією. Bukovinian Mathematical Journal, 3(3-4). Retrieved from https://bmj.fmi.org.ua/index.php/adm/article/view/128
Keywords: parabolic system of differential equations; small diffusion; stability; traveling waves; spin combustion; Hutchinson equation